Estrategias bioclimáticas para el espacio público del sector 1 del municipio de Palmira. (2021)
This document presents a research project whose central theme is the Public space, seen from the Bioclimatic perspective, I understand that it is a factor fundamental when creating a space that provides thermal comfort for users, added to this, climate change appears as a factor that evidences the need to generate a space that responds to the climatic factor in which a project is implemented, as given with rising temperatures.